Anal atresia and the Klein-Waardenburg syndrome. Issue 3 (June 1981) - Nutman, J; Nissenkorn, I; Varsano, I; Mimouni, M; Goodman, R M
Abstract : A 3-month-old male infant with type I Klein-Waardenburg syndrome with an imperforated anus and a perineal fistula is reported. The possible association of this gastrointestinal malformation with the KW syndrome is discussed.